Il teatro in prosa del Cataplus - Martina Tosello (Annali Online dell'Università di Ferrara. Sezione Lettere)
The “theatricality” often attributed to Lucian’s work is not limited to thematic and textual references; it is also due to a certain Second Sophistic tendency to spectacularise and the author’s need to facilitate the reception of the Dialogues by appealing to the audience’s paideia and the ability of the theatre to psychagogein, that is exerting a directive influence upon the soul. Hence, an analysis has been carried out on Cataplus (a dialogue which is particularly rich in dramatic action) to identify the rhetorical instruments used by Lucian to stimulate the audience’s imagination enargeia, akribologia, ekphrasis) thereby turning his work into a pièce, a sort of inner spectacle with every single element taking its own tangible shape. According to Lucian’s cynical, satirical vision, the tragedy of human existence is converted into comedy wherein laughter allows to alter one’s outlook on reality as a fast track to virtue.